Updated Evidence and Policy Developments on Reducing Gun Violence in America - Vernick, Jon S.; Webster, Daniel W.; Project Muse; Project Muse. (Project Muse, 2018)
In 2013--in the wake of the tragic shooting at Sandy Hook Elementary School--Johns Hopkins University Press published Reducing Gun Violence in America, a collection of essays written by the world's leading experts on gun violence. Updated Evidence and Policy Developments on Reducing Gun Violence in America follows up on the state of American gun violence by analyzing new data, research, and policy developments one year after Sandy Hook. Over the course of ten substantive chapter addendums, contributors bring readers up-to-date on such varied topics as mental illness, domestic violence, background checks, illegal gun sales, and personalized guns. They describe the recent policy measures that have been enacted and suggest additional approaches that may help stem the violence. An essential companion to Reducing Gun Violence in America, the reliable, empirical research and legal analysis in this e-book will help lawmakers, opinion leaders, and concerned citizens identify policy changes to address gun violence, which takes an average of more than 80 lives every day in the United States.
Introduction / Daniel W. Webster and Jon S. Vernick -- 3. Update : thinking differently about mental illness, violence risk, and gun rights / Jeffrey W. Swanson and Allison G. Robertson -- 4. Update : enactment of legislation to protect victims of domestic violence : a story of state successes / April M. Zeoli and Shannon Frattaroli -- 6. Update : broadening denial criteria : new developments / Garen J. Wintemute -- 7. Update : comprehensive background checks : new evidence and rethinking "comprehensive" / Garen J. Wintemute -- 8. Update : preventing the diversion of guns to criminals through effective firearm sales laws / Daniel W. Webster, Jon S. Vernick, Emma E. McGinty, and Ted Alcorn -- 10. Update : adequate oversight of licensed firearm dealers remains a problem / Jon S. Vernick and Daniel W. Webster -- 11. Update : enforcing federal laws against firearms traffickers : policy and legislative progress in 2013 / Anthony A. Braga and Peter L. Gagliardi -- 13. Update : personalized guns progress report / Stephen P. Teret -- 18. Update : the Second Amendment / Lawrence E. Rosenthal and Adam Winkler -- 19. Update : Public opinion on gun policy following the Newtown mass shooting and the disconnect with political action / Emma E. McGinty, Daniel W. Webster, Jon S. Vernick, and Colleen L. Barry.
"A Johns Hopkins digital short."
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Violent crimes -- United States -- Prevention; Firearms -- Government policy -- United States; Gun control -- United States; Electronic books; Electronic books